THE ‘SLIPPERY SLOPE FRAMEWORK’ APPROACH: FEARS AND CARES THAT AFFECT VOLUNTARY TAX COMPLIANCE - Khasanah, Uswatun; Tofan, Ali; Mufarokhah, Nur; Zainab; Vitriya, Rezza (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2024)
We conducted research on the role of tax audits, rewards, and tax socialization on voluntary tax compliance. Referring to the theory of taxpayer behavior 'slippery slope theory' which predicts tax compliance behavior at KPP Pratama Kepanjen. This study uses a fear approach that is reflected in tax audits and a caring approach that is reflected in rewards and tax socialization. The results of the study show that voluntary tax compliance will increase if taxpayers have the possibility to conduct a tax audit from the authority. Different results are shown by rewards that have no effect on voluntary tax compliance. Meanwhile, tax socialization can increase voluntary tax compliance.